Capacity Building for Lecturers and Students of Instituto Superior Crystal Dili, Timor Leste in Emergency Handling in Pre-Hospital and Intra-Hospital Settings - Sriyono, Sriyono; Haryanto, Joni; Syahri, Alfi; Susilawati, Desi; Harigustian, Yayang; Sari, Purwanti Nurfita; Effi, Maria Carmelinda Olgita Atu; Dua, Yohana Hendrika (INSTITUT KESEHATAN DELI HUSADA, 2024)
Emergency conditions can occur anywhere and at any time, threatening the safety and lives of victims regardless of age. Such events can happen at home, work, school, or public places, necessitating knowledge and skills for first responders. This community service aims to enhance the knowledge of lecturers and students on Emergency Handling in Pre-Hospital and Intra-Hospital settings. The international community service on Emergency Handling in Pre-Hospital and Intra-Hospital took place offline at Instituto Superior Cristal, Dili, Timor Leste, from July 22-24, 2024. A total of 300 lecturers and students participated. The sessions were conducted by lecturers and students from the Faculty of Nursing, Universitas Airlangga. Key topics included